Effect of Fixed Orthodontic Appliances and Filgrastim on Body Weight A Murine Model (Mustansiria Dental Journal, 2024)
Aim: The aim was to assess how orthodontic treatment and Filgrastim injections affect body weight in Wistar albino rats during and after treatment. Materials and Methods: Orthodontic tooth movement (OTM) was induced using the appliances, followed by a 14-day healing period after their removal. This study adopted a "split-mouth design," with OTM occurring exclusively on the left side of the mouths of 55 male Wistar albino rats, divided into five groups: A (no Filgrastim during active OTM, n = 12), B (Filgrastim during active OTM, n = 11), C (no Filgrastim during active OTM and healing, n = 11), D (Filgrastim during active OTM and healing, n = 11), and E (no Filgrastim during active OTM and healing, n = 10). Filgrastim (10 µg/kg) was administered intraperitoneally three times weekly throughout the trial. A force of 100 grams was applied mesially to the first molar using a fixed orthodontic device. Results: Rats exhibited significant body weight reduction (p < 0.05) after the first week, followed by gradual, slight weight recovery post-appliance removal. However, their final weight did not return to baseline. Conclusion: Orthodontic intervention significantly reduced rat body weight, with Filgrastim showing minimal to no effect.